THE ROLE OF NOVICE VOTERS IN PARTICIPATORY ELECTION SUPERVISION - Aji Nurfauji; Uu Nurul Huda (Universitas Muhammadiyah Mataram, 2024)
According to Article 101 of Law Number 7 of 2017, the Election Supervisory Agency is responsible for supervising the electoral democracy process, starting from the Legislative Election (PILEG), Regional Election (PILKADA), and Presidential Election (PILPRES). As a constitutional responsibility to oversee elections, innovation is needed to increase the value of supervision to ensure quality elections. New initiative carried out by Bawaslu South Bangka Regency to oversee elections and increase public participation will be explained in this paper. This study uses an analytical descriptive approach and uses primary data obtained from the actions of the author team. The study concluded that the election supervision class program, which creates participatory surveillance agents in all sub-districts, is very effective in increasing voter participation and political awareness, especially in terms of initial elections.